PENGARUH BEBAN KELUARGA, STRATEGI KOPING DAN SELF EFFICACY TERHADAP KEMAMPUAN KELUARGA DALAM MERAWAT PASIEN SKIZOFRENIA DI WILAYAH KERJA PUSKESMAS BAROS KOTA SUKABUMI - Rani Indriani Kusumah (JURNAL KESEHATAN INDRA HUSADA, 2022)
The number of mental disorders every year has increased very significantly and continues to grow. Schizophrenia is a chronic psychotic disorder that has an impact not only on the sufferer but also on his family so that the ability of the family is needed in caring for family members. Family ability is influenced by family burden, coping strategies and self efficacy. The purpose of the study was to determine the effect of family burden, coping strategies and self-efficacy on the ability of families to treat schizophrenia patients in the Baros Public Health Center, Sukabumi City. This study uses a correlational method with a cross sectional approach. The population and sample were all families who cared for schizophrenia patients in the Baros Public Health Center, Sukabumi City, with 30 respondents using total sampling technique. The instrument used for the family burden variable is the Zarit Burden Interview (ZBI), for self-efficacy using the General Self Efficacy instrument, for coping strategies using Brief COPE, while measuring the dependent variable, namely the family's ability, refers to a questionnaire and observation sheet modified from FAD ( Family Assessment Device). Statistical analysis in this study using simple regression analysis and multivariate analysis using multiple regression analysis. The results showed that there was an influence of family burden, coping strategies and self-efficacy on the family's ability to treat schizophrenia patients in the Baros Public Health Center, Sukabumi City.